Islamic Digital Communication Ethics in the Hijabsters Phenomenon: Social and Cultural Challenges on Social Media - Deryl Ardica; Ema Hidayanti (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
This study aims to describe the ethical challenges of digital communication in Islam as encountered in the phenomenon of hijabsters on social media, and to offer solutions to the emerging issues. Employing a qualitative method with a descriptive approach, the study is supported by non-participant digital observation and qualitative content analysis. Data were collected through observations of hijabsters posts on Instagram, TikTok, and X (formerly Twitter), which were then categorized based on recurring themes, such as clothing style, messages in captions, use of Islamic symbols, and public responses in the comments section. The findings reveal that the hijabsters phenomenon raises several ethical concerns, including violations of modesty norms, the commodification of Islamic symbols, and covert exhibitionism in digital spaces. The diverse audience responses ranging from praise to sharp criticism reflect a shifting boundary of norms and evolving public interpretations of Muslim female identity. This study highlights the urgent need for clearer regulations regarding religious content online, as well as the importance of digital literacy education that integrates Islamic values such as modesty, politeness, and media responsibility. Practically, the study serves as a reference for educators, parents, and Muslim communities in fostering ethical digital understanding among youth. Theoretically, it contributes to the development of Islamic digital communication ethics discourse within the context of new media culture, while enriching scholarly perspectives on religious identity and self-expression in the digital era.